Patient-Specific iPSC-Based Models of Huntington’s Disease as a Tool to Study Store-Operated Calcium Entry Drug Targeting - Vigont, Vladimir; Nekrasov, Evgeny; Shalygin, Alexey; Gusev, Konstantin; Klushnikov, Sergey; Illarioshkin, Sergey; Lagarkova, Maria; Kiselev, Sergey L.; Kaznacheyeva, Elena (Frontiers in Pharmacology, 2018)
Neurodegenerative pathologies are among the most serious and socially significant problems of modern medicine, аlong with cardiovascular and oncological diseases. Several attempts have been made to prevent neuronal death using novel drugs targeted to the cell calcium signaling machinery, but the lack of adequate models for screening markedly impairs the development of relevant drugs. A potential breakthrough in this field is offered by the models of hereditary neurodegenerative pathologies based on endogenous expression of mutant proteins in neurons differentiated from patient-specific induced pluripotent stem cells (iPSCs). Here we study specific features of store-operated calcium entry using an iPSCs-based model of Huntington’s disease (HD) and analyze the pharmacological effects of a specific drug targeted to the calcium channels. We show that store-operated calcium entry in GABA-ergic striatal medium spiny neurons (GABA MSNs) was mediated by currents through at least two different channel groups, ICRAC and ISOC. Both of these groups were upregulated in HD neurons compared with the wild type neurons. Thapsigargin-induced intracellular calcium store depletion in GABA MSNs resulted in predominant activation of either ICRAC or ISOC. The potential anti-HD drug EVP4593, which was previously shown to have neuroprotective activity in different HD models, affected both ICRAC and ISOC.